2005
DOI: 10.1002/prep.200500020
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the Synthesis of NTO in Nitric Acid

Abstract: The nitration kinetics of 1,2,4-triazol-5-one in 70 -100% nitric acid were investigated. Formation of N-nitro-1,2,4-triazol-5-one under these conditions was observed, and its influence on the total process was studied. The activation energies of formation and decomposition of N-nitro-1,2,4-triazol-5-one and of the nitration of 1,2,4-triazol-5-one were determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 4 publications
0
30
0
Order By: Relevance
“…Partial area log(A/s -1 ) aEa/kJ mol -1 Fig. 6 Dependence of the apparent activation energy ( a E a ) and preexponential factor log (logA) on the conversion degree (a) of PYX sample on the basis of DSC measurements in a hermetic pan Origin of PYX thermal stability investigation with calorimetric and spectroscopic methods 2051 3-nitro-1,2,4-triazol-5-one [23] and the measured pKa of its compounds is 3.98 [24]. Dissociation ability of PYX N-H protons was confirmed by synthesis of its organic and inorganic salt [1].…”
Section: Nuclear Magnetic Resonance Studymentioning
confidence: 99%
“…Partial area log(A/s -1 ) aEa/kJ mol -1 Fig. 6 Dependence of the apparent activation energy ( a E a ) and preexponential factor log (logA) on the conversion degree (a) of PYX sample on the basis of DSC measurements in a hermetic pan Origin of PYX thermal stability investigation with calorimetric and spectroscopic methods 2051 3-nitro-1,2,4-triazol-5-one [23] and the measured pKa of its compounds is 3.98 [24]. Dissociation ability of PYX N-H protons was confirmed by synthesis of its organic and inorganic salt [1].…”
Section: Nuclear Magnetic Resonance Studymentioning
confidence: 99%
“…A similar strategy might work for the synthesis of 5-nitrimino-3-nitro-1,2,4-triazole (Scheme 4). When NTO is dissolved in concentrated nitric acid reactive by-products are formed [3,28]. If ANTA is mixed with concentrated nitric acid similar reactions might occur and the proposed route for 5-nitrimino-3-nitro-1,2,4-triazole (Scheme 4) would need to be modified.…”
Section: Synthetic Routesmentioning
confidence: 99%
“…where α = 1.0462, β = 1.198 × 10 −4 g/(cm 3 (kJ/mol) 2 ), and γ = −0.1586 g/cm 3 . The geometry of the molecule was optimized at the B3LYP/6-31G(d,p) level.…”
Section: Crystal Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…The nitration of TO using concentrated nitric acid (85-100 %) showsl ittle dependence on the ratio of the reagents, the temperature, and the dilution of the reactant acid [35b,41].Z barsky and Yudin analyzed the kinetics and mechanism of the nitration of TO in 72-100 %H NO 3 [42] and found that the nitration can be describedb yp seudofirst-order reaction kinetics. At HNO 3 concentrations exceeding 77 %, 1-nitro-1,2,4-triazol-5-one (N-NTO) is formed within the first minuteso fthe reaction.…”
mentioning
confidence: 99%